Simultaneous electrodeposition of electrochemically reduced graphene oxide-binary metal chalcogenide composites to enhance photoelectrochemical performance - KOCA, ATIF; BUDAK, ÖZLEM; UĞUZ NELİ, ÖZLEM (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
In this study, a facile and one-step simultaneous electrodeposition of the composite thin films bearing binary metal chalcogenides (CdxZn1-xS (x = 0.0, 0.2, 0.5, 0.8, 1.0)) and electrochemically reduced graphene oxide (RGO) was carried out via repetitive cyclic voltammetry (rCV). Then their photoelectrochemical (PEC) performances were investigated under the solar light irradiation to find out the optimized composition of the composites. Immobilization of Cd1-xZnxS nanoparticles among the RGO sheet with the rCV confined the Cd1-xZnxS nanoparticles between the RGO sheets, which prevented leakage of these particles from the electrode surface and contributed to the increase of active sites for the PEC reaction. PEC results showed that increasing x from 0 to 0.8 in CdxZn1-xS composition boosted the photocurrent density, reaching from 25 mA cm(-2) to 438 mA cm(-2). Incorporation of RGO to the structure increased the conductivity and prevented the photocorrosion of Cd0.8Zn0.2S, thus, RGO(0.25)-Cd0.8Zn0.2S enhanced the photocurrent density from 0.44 mA cm(-2) (as-synthesized Cd0.8Zn0.2S) to 1.38 mA cm(-2). (C) 2021 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Cadmium zinc sulfide; Cyclic voltammetry; Electrodeposition; Photoelectrochemical hydrogen production; Reduced graphene oxide; ONE-POT SYNTHESIS; PHOTOCATALYTIC ACTIVITY; EFFICIENT PHOTOANODE; HYDROGEN-PRODUCTION; CADMIUM-SULFIDE; THIN-FILMS; WATER; CDS; GROWTH; RGO